RESEARCH ON WELD FAILURE ANALYSIS OF PLUNGER OF ABAQUS MULTISTAGE CYLINDER - LIU YanPing; LIN FangJun; WANG HaiLong; WANG GuoYuan (Jixie qiangdu)
The failure of the welding seam between the end of 100 plunger and the shaft head of the multi-stage hydraulic cylinder used in off-highway dump truck occurred in the mining area. Through the chemical composition, weld microstructure and microhardness of the weld of the failed parts and the micro detection of the fracture weld, the failure reason was found out. Optimized design was carried out from the aspects of parts material, weld structure, process control and part structure. Based on ABAQUS software, fatigue simulation analysis and bench test were carried out on the weld, which effectively verified the consistency of design optimization and bench test and reduced the failure rate. It has certain guidance and reference significance for similar products.